ПРОСТРАНСТВЕННЫЙ АНАЛИЗ В РЕГИОНАЛЬНОМ ИССЛЕДОВАНИИ ТРАНСПОРТА С ИСПОЛЬЗОВАНИЕМ ГИС-ТЕХНОЛОГИЙ - Сёмина (Syomina Irina) Ирина Александровна; Фоломейкина (Folomeykina Larisa) Лариса Николаевна (Географический вестник=Geographical bulletin, 2017)
Исследуется функционирование регионального транспорта с использованием ГИС-технологий. Проводится пространственный анализ развитости дорожной сети Республики Мордовия и воздействия автомобильного транспорта на окружающую среду. Представлена типология административных районов Мордовии по транспортным показателям и степени транспортной нагрузки на территорию. SPATIAL ANALYSIS IN REGIONAL EXPLORATION OF TRANSPORT BY USING GIS-TECHNOLOGIES Geographic information system (GIS) technologies can be used for working with spatial data on subject of transport. Different kinds of transport are being characterized by their specific functions, which can be determined by using GIS. The problem of data’s selection for spatial analysis has special difficulty. In the abstract several versions of data’s estimating are tested. In complex approach for solving problems of regional automobile transport’s clustering analysis was applied. Also, estimating indicators of density and configuration of Mordovian administrative districts’ transportation network were used. Researchers of ecological problems caused by automobile transport functioning, usually, use data of pollution rate of motor vehicle and road-net density. In this abstract the authors have used algorithm of estimate classification for construction of territorial unit’s typology. On the date base that receives by tools of ArcView GIS-packet, several maps were created. They reflect specifics of Mordovian Republic’s road-net and transportation’s influence on population life activity. Proposed modeling of typological and estimating characteristics of Mordovian Republic’s roadnet can be used for solving problems of regional automobile transport functioning and spatial governing.